SATISFACTION OF GUESTS AT THE GASTROENOLOGICAL OFFER IN BELGRADE - Jankovic, Ivana; Ciric, Milos (The Business of Tourism, 2020)
Tourism is one of the areas that has begun to develop in the last few year and one of the main reasons for that represent the intensive development of gastronomy. The development of gastronomy and a quality offer of food and drinks is one of the means for ensuring the quality of the guest in a restaurant. Special attention in the gastronomic area is represented by the gastroenolic offer, ie the offer of food and wine, which requires special care of the food on the plate and the wine that is served with it. This paper will present the results obtained after conducting research in several Belgrade restaurants in order to examine the satisfaction of users with their gastroenological offer. Over the past years, the literature has been enriched by numerous studies which talk about the factors that affect on the level of satisfaction with gastroenological offers and the list of the most important factors includes gender, age, education, occupation, family status. After detailed analysis of the obtained results, it has been concluded that the guests of Belgrade restaurants are satisfied with the gastrooenological offer, but a small percentage of respondents, who are not satisfied with this offer, increase the need for improve catering services and also gastroenological offer.
Keywords: gastronomy, gastroenology, food, wine, gastroenological offer, customer satisfaction